Managerial Objectives, Capital Structure, and the Provision of Worker Incentives - Garvey, Gerald T.; Swan, Peter L. (Journal of Labor Economics, 1992)
Worker incentive schemes are invariably assumed to be administered by an owner-entrepreneur who has an incentive to understate worker performance after the event. While tournaments can overcome this problem, they discourage cooperation between workers. We show that a professional manager concerned with equality between workers and with avoiding bankruptcy rather than maximizing shareholder wealth will conduct a tournament that preserves individual effort incentives while promoting cooperation between workers. The theory predicts lower debt levels and more compressed pay scales as cooperation becomes more important. In the limit this becomes a group bonus scheme, supported by "blue-chip" debt.